(untitled) (Academia Science Repository, 2023)
Vocabulary is the cornerstone of language, however persons learning a language may not be skilled at using techniques to help with word memorization. The comparison of the effects of the semantic mapping strategy on the vocabulary mastery of forty Uzbek learners was the main objective of this work. A control group that received standard direct translation training and a treatment group that received semantic mapping instruction randomly split the participants into two groups. A pre-test and post-test were administered to both groups in order to evaluate the method’s efficacy. The results show that when the semantic mapping technique was applied, the participants’ vocabulary learning greatly varied.